Increasing Maternal Employment Influences Child Overweight/Obesity Among Ethnically Diverse Families. (July 2018) - Ettinger, Anna K.; Riley, Anne W.; Price, Carmel E.
Maternal employment is associated with child overweight/obesity, but the mechanisms influencing this relationship are not clear among diverse populations. We examined the effects of employment and parenting variables on child overweight/obesity among low-income Black and Latino families. Using longitudinal data from the Three-City Study, we analyzed the effects of maternal employment and nonstandard work schedule on child overweight/obesity and examined time away from children, parenting stress, and parenting practices as potential mediators. Mothers who increased their work hours during preschool years had children with approximately 2.6 times the odds of overweight/obesity compared to mothers who did not change their work status. Time away from children partially mediated the association between employment and child overweight/obesity. More consistent family routines were associated with a 61% decline in odds of child overweight/obesity. Early increases in maternal employment elevated the odds of child overweight/obesity, but regular family routines reduced the odds of overweight/obesity among school-age children in low-income Black and Latino families.